Improving the Structural Reliability of Steel Frames Using Posttensioned Connections - Edén Bojórquez; Arturo López-Barraza; Alfredo Reyes-Salazar; Sonia E. Ruiz; Jorge Ruiz-García; Antonio Formisano; Francisco López-Almansa; Julián Carrillo; Juan Bojórquez (Advances in Civil Engineering)
In this paper, various moment-resisting steel frames (MRSFs) are subjected to 30 narrow-band motions scaled at different ground motion intensity levels in terms of spectral acceleration at first mode of vibration SaT1 in order to perform incremental dynamic analysis for peak and residual interstory drift demands. The results are used to compute the structural reliability of the steel frames by means of hazard curves for peak and residual drifts. It is observed that the structures exceed the threshold residual drift of 0.5%, which is perceptible to human occupants, and it could lead to human discomfort according to recent investigations. For this reason, posttensioned connections (PTCs) are incorporated into the steel frames in order to improve the structural reliability. The results suggest that the annual rate of exceedance of peak and residual interstory drift demands are reduced with the use of PTC. Thus, the structural reliability of the steel frames with PTC is superior to that of the MRSFs. In particular, the residual drift demands tend to be smaller when PTCs are incorporated in the steel structures.